Breastfeeding in Pediatric Acute-Onset Neuropsychiatric Syndrome: An Italian Observational Study - Murciano, Manuel; Biancone, Davide Maria; De Luca, Francesca; Piras Marafon, Denise; Guido, Cristiana Alessia; Spalice, Alberto (Frontiers in Pediatrics, 2021)
Objective Pediatric acute-onset neuropsychiatric syndrome (PANS) is a condition defined by sudden onset of obsessive-compulsive symptoms and/or severe eating restrictions, along with at least two other cognitive, behavioural, or neurological symptoms. Its pathogenesis is unknown but it seems triggered by infections, metabolic disturbances, and other inflammatory reactions. PANS represents a neuro-developmental problem and infant feeding can play a role. Breast milk is the ideal food for infants and influences children’s brain, cognitive, and socio-emotional development. Methods We enrolled 52 children diagnosed with PANS. We interviewed their parents in order to investigate perinatal history, infant feeding, neurologic development and confounding factors like socio-economic status and region of origin. We sub-grouped PANS patients into three subset: who only received human milk (HMO), who only received infant formula and who received mixed feeding. Results The cohort is composed of 78,9% of males, median age of 11 years (range 7-17). We found some neuro-development problems (13,5%): walking disorders, ASD, ADHD, oppositional attitude and delayed psychomotor development. We found scholar performance deficits (25%), including language problems like dysgraphia, dyslexia, dyscalculia. The achievement of some milestones in the development of the infant is affected in the 73,1% of cases. Breastfeeding is not homogeneously practiced in Italy because of social, economic and cultural phenomena. The richest and the poorest families (100%) in the sample choose breastfeeding, probably with a different approach and for different reasons (awareness or need). In the group of PANS patients fed with HMO, comparing to the rest of the patients, we registered fewer cases of growth problems (0vs12,9%; p-value 0,14), school performance problems or needing of school support (19,1%vs29%; p-value 0,42), and a delay in the age of babbling/speaking (range 4-20vs7-36 months; p-value 0,066). Conclusion This is the first study that investigates the role of breastfeeding in the development of PANS. Promoting breastfeeding is important in general population and also in PANS patients because it have important social and global health impact, also during adult life. Further studies with a bigger population are needed to investigate the mechanisms underlying PANS and the role that breastfeeding may play in their short- and long-term neurodevelopment.